Dominance and servitude. Hegel's criticism of Fichte in the paper on the Difference - Rendón Arroyave, Carlos Emel (Estudios de Filosofía, 2006)
This article is a revision of the criticism that Hegel makes to conception of nature that underlies Fichtes Theoretical and Practical Philosophy. In Hegel's Differences Between the Philosophical System of Fichte and Schelling (1801), Hegel directs his reflection to the relation between Dominance and Submission that Fichte's Philosophy establishes between Reason and Nature. And this to such a degree, that it turns out to be the base for the deduction of Natural Right, whose main purpose is to show the possibility of Auto-conscience and, with it, that of the Human Community in general. Hegel shows that Fichte's deduction is contradictory, and from his critique he will lay down a new concept of Nature.